Cell-free protein synthesis using multiply-primed rolling circle amplification products. (July 2009) - Kumar, Gyanendra; Chernaya, Galina
Utilizing in vitro transcription and translation (IVTT) to produce small quantities of proteins is convenient but requires a significant supply of pure template DNA. This can be cumbersome, particularly when the method is used for many different templates in a high-throughput manner. Multiply-primed rolling circle amplification (RCA) with ϕ29 DNA polymerase is a simple way to generate large amounts of DNA; however, the products of this amplification method have interruptions in both strands and branched structures. In this study, we tested whether RCA-generated DNA can serve as the template for in vitro transcription. We found that RCA DNA–generated transcripts work in coupled in vitro translation with nearly the same efficiency (per nanogram of DNA) as those obtained from purified plasmid. We propose a convenient, single-tube format for template amplification, transcription, and translation.